Flora of Espírito Santo: Sloanea (Elaeocarpaceae) - Maia, Talita Antunes [UNESP]; Sampaio, Daniela [UNESP] (FapUNIFESP (SciELO), 2019)
Elaeocarpaceae is represented by 15 genera with approximately 500 species, which are distributed in tropical and subtropical regions, with the exception of the African and European continents. Sloanea is considered the most numerous tropical genus of the family, and presents approximately 150 species described in both Old World and New World. Sloanea is characterized by the presence of buttressed roots, pulvinate petiole, monomerous flowers and capsule fruit covered with thorns. Seven species of the genus were recognized in the state: Sloanea eichleri, Sloanea fasciculada, Sloanea garckeana, Sloanea guianensis, Sloanea hirsuta, Sloanea retusa and Sloanea obtusifolia.
Flora do Espírito Santo: Sloanea (Elaeocarpaceae)
Keywords: Atlantic forest; Biodiversity; Brazil; Morphology; Taxonomy